Gc/ms analysis, in vitro antisalmonellal activity and mechanism of action ethanol leaves extract of dissotis thollonii cogn. (melastomataceae) against some pathogenic salmonella sp. - Fodouop Chegaing Pierre (International Journal of Phytomedicine, 2019)
Background: Salmonella spp, which is a group of Gram-negative bacterial pathogens causing significant morbidity and mortality worldwide. In the Cameroon as well as in many part of the world, plants are used for the treatment of various diseases such as typhoid fever. The aim of the present study was to investigate the in vitro anti-salmonella activity and the mechanisms of action of the ethanol extract of Dissotis thollonii against some Salmonella sp. Methods: The microdilution technique was used to determine MIC and MBC whereas gas chromatography/mass spectrometry (GC/MS) was used to identify some components of the ethanol extract. The antibacterial mechanism of this extract on Salmonella Typhi (ATCC 6539) was systematically investigated by examining its effect on macromolecules (DNA, RNA, protein) synthesis, the time kill assay and bacteriolysis assay. Results: The ethanol extract of Dissotis thollonii showed MICs ranging from 64 to 256 μg/mL. This extract induced lysis of S. Typhi ATCC6539 and the time-kill assay revealed a reduction of about 4log10 of the total number of CFU ml-1. Additionally, the quantity of bacterial protein, DNA and RNA decreased significantly after treatment with this extract. GC/MS revealed the presence of 7 compounds, identified using NIST library. Conclusion: The results of this study show that the antisalmonellal potential of ethanolic extract of D. thollonii is mainly caused by inhibition of bacterial macromolecule synthesis (DNA, RNA and protein).